2005
DOI: 10.1007/s10194-005-0209-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic daily headache in a paediatric headache centre

Abstract: The prevalence and the clinical features of chronic daily headache (CDH) were studied in 968 children and adolescents observed during a period of one year in the Headache Centre of the Anna Meyer Paediatric Hospital of Florence. Nine hundred and fortyfour patients (97.52%) had primary headache according to ICHD-II, 24 subjects had secondary headache and 56 patients had CDH (5.93% of primary headaches). The mean age of subjects with CDH was higher than general (13.5 vs. 11.5 years), with a female preponderance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…There was a significant excess of females over males (48 vs 22). A similar preponderance of females over males has been reported by others 9,10,14–22 . In a selective population‐based study from Taiwan, Wang et al found the 1 year estimated prevalence of CDH to be 0.8% in males and 2.4% in females 15 …”
Section: Discussionsupporting
confidence: 70%
“…There was a significant excess of females over males (48 vs 22). A similar preponderance of females over males has been reported by others 9,10,14–22 . In a selective population‐based study from Taiwan, Wang et al found the 1 year estimated prevalence of CDH to be 0.8% in males and 2.4% in females 15 …”
Section: Discussionsupporting
confidence: 70%
“…Around 87% of the patients had some form of migraine both in the first and second assessments. Other studies conducted at the tertiary care found that the prevalence of migraine at this setting ranges from 33 to 80% [3][4][5][6]8 . A past study conducted in our clinic diagnosed migraine in 79.2% of the patients 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, tension-type headache (TTH) is the most common headache type, followed by migraine 1,2 . In the tertiary care, however, migraine and chronic daily headaches (CDH), are far more common than TTH [3][4][5][6][7][8] . CDHs do not represent a distinct nosologic entity, as per the second edition of the International Classification of Headache Disorders (ICDH-II) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Most pediatric studies suggest that the incidence of MOH is relatively low, although there are a few exceptions. 5,[8][9][10][11][12][14][15][16]23,39 The absence of well defined criteria for children may explain some of the differences between studies, although selection bias and geography may also play a role. Hence, pharmacologically based criteria are needed for children.…”
Section: Chronic Migraine (Appendix Code 151)mentioning
confidence: 99%
“…11,14,15,17,19,20,27,32 The provisos for the diagnosis of any of the primary headache disorders include the caveat: "History and physical and neurological examinations do not suggest any of the disorders listed in groups 5-12…or (such disorders are) ruled out by appropriate investigations…" 32 Four issues that are the subject of continuing debate will be discussed.…”
Section: Classification Of Cdhmentioning
confidence: 99%